Madame Bovary’yi beden diliyle okumak - GENÇ, NALAN (Border Crossing, 2016)
This study aims at discovering Emma’s expectations and her search for answers about her existence in the universe rather than analyzing the author’s style or the narration. This aim is attained by evaluating the real meaning of the narrative through body language and scrutinizing the agonies of Emma’s, a woman’s soul in non-verbal communication, rather than by analyzing the words of Emma or her surroundings. We attempted to present how and how much we could express the verbal meanings in the novel with a non-verbal language